Hemocompatibility evaluation in vitro of methoxy polyethyleneglycol-polycaprolactone copolymer solutions - Hu, Q.; Zhang, Y.; Wang, C.; Xu, J.; Wu, Ping; Liu, Z.; Xue, W. (2016)
Amphiphilic block copolymer methoxy polyethyleneglycol–polycaprolactone (mPEG–PCL) has attracted interest in the biomedical field, due to its water solubility and biodegradability. Nevertheless, the blood safety of mPEG–PCL copolymers has not been investigated in detail. Because mPEG–PCL copolymers introduced in vivo would inevitably interact with blood tissue, an investigation of possible interactions of mPEG–PCL with key blood components is crucial. We studied the effects of two mPEG–PCL copolymer solutions on blood coagulation, the morphology and lysis of human red blood cells (RBCs), the structure of plasma fibrinogen, complement activation, and platelet aggregation. We found that higher concentrations of the mPEG–PCL copolymers impaired blood clotting, and the copolymers had little impact on the morphology or lysis of RBCs. From the spectroscopy results, the copolymers affected the local microstructure of fibrinogen. The copolymers significantly activated the complement system in a concentration-dependent way. At higher concentrations, the copolymers impaired platelet aggregation, which may have been mediated by an inhibition of the arachidonic acid pathway. These findings provide important information that may be useful for the molecular design and biomedical applications of mPEG–PCL copolymers.